LONG-RUN INDUSTRY EFFECT ON STOCK RETURN: AN EMPIRICAL EVALUATION OF SELECTED NIGERIAN BANKS - Arewa, A; Nwakanma, P C (European Scientific Journal, ESJ, 2013)
﻿﻿The study develops a fresh econometric equation to estimate the nature of the relationship between banking industry activities and stock market returns in Nigeria. The equation utilizes annual data sourced from the various volumes of Nigerian Stock Exchange (NSE) Fat books, NSE Daily Official List and annual reports of the selected banks for a period of 25 years ranging from 1984 to 2009. Our findings reveal that the activities of the banking industry and stock market return maintain a long-run relationship. Furthermore, we discover that an increase in earning produces a positive multiplier effect on stock market return; while retention of earning for acquisition of assets and high level of debt/leverage ratio is found to be detrimental to stock prices here in Nigeria.